THE RELATIONSHIP BETWEEN DIET AND NUTRITIONAL STATUS WITH THE INCIDENCE OF STUNTING IN CHILDREN AGED 2–5 YEARS IN THE WORKING AREA OF THE MAWASANGKA HEALTH CENTER - Nurhikmah, Nurhikmah; Evawati Uly; Dyah Tahir; Muliyana; Erwin, Erwin (International Journal of Social Science, 2025)
Background: Stunting is a chronic nutritional problem caused by a lack of nutritional intake over a long period of time and is often associated with an inadequate diet. This condition has a serious impact on the physical growth, cognitive development, and productivity of children in the future. Objective: This study aims to determine the relationship between diet and nutritional status and the incidence of stunting in children aged 2–5 years in the working area of the Mawasangka Health Center. Methods: This study used a cross sectional design with a sample of 80 children aged 2–5 years who were selected by purposive sampling. It will be held in November 2025. Data were collected using dietary questionnaires, anthropometric measurements (weight, height), and maternal interviews. Data analysis was carried out by Chi-Square test. Results: The results showed that there was a significant relationship between diet and stunting incidence (p=0.001) and between nutritional status and stunting incidence (p=0.003). Children with an unbalanced diet are 3.5 times more likely to experience stunting than children with a good diet. Conclusion: Diet and nutritional status have a significant relationship with stunting events. Efforts are needed to improve balanced nutrition education for families to reduce stunting rates in the work area of the Mawasangka Health Center